(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This study explores various strategies that enable the integration of Pancasila values into the country’s economic system, particularly in efforts to empower the people’s economy and reduce dependence on significant capital. Study Design/Methodology/Approach: This study utilises library research to explore and integrate existing theoretical perspectives, both from classical and contemporary literature, with integrative and connective analysis across various literature so that it does not merely present separate theoretical perspectives. Findings: The Pancasila economy can serve as a national strategic plan to undermine the dominance of exploitative capitalism by introducing a new development paradigm based on social justice, economic sovereignty, and ecological sustainability. It can also function as a socio-economic engineering instrument that strengthens social cohesion, reinforces state legitimacy, and paves the way for Indonesia to emerge as a pioneer of alternative paradigms on the international stage. The economy can also provide creativity for other developing countries in regulating a more humanistic, inclusive, and equitable world economy. Originality/Value: The Pancasila economy not only strengthens the nation’s independence and competitiveness through the management of resources that favour the people, the empowerment of MSMEs, and the fair redistribution of assets, but also presents a global alternative that challenges the paradigm of exploitative capitalism by placing social solidarity, cooperation, and ecological sustainability as the main foundations of economic development.